HLA Alleles and Lung Cancer in a Turkish Population - Özbek, N.; Birinci, A.; Karaoǧlanoǧlu, O.; Çoban, A.Y.; Okumuş, B.; Cakir, S.; Durupínar, B. (King Faisal Specialist Hospital and Research Centre, 2004)
Background: The concept of genetic factors playing a role in the pathogenesis of lung cancer has gained increased attention. The present study was undertaken to examine the question of HLA association with lung cancer and to investigate the effect of HLA on survival time. Methods: The distribution of HLA class I (A, B, C) antigens and class II (DR, DQ) alleles were studied in 81 unrelated Turkish patients with lung cancer. The HLA status of patients was compared with that of a control group consisting of 117 ethnically matched healthy donors. HLA class I antigens were studied by Terasaki's microlymphocytotoxicity test and HLA class II alleles were studied by polymerase chain reaction with the sequence specific primer (PCR-SSP) low resolution method. Results: Only the frequencies of HLA-B51 and -DRB1 * 15 were lower in the lung cancer group compared with the healthy control patients. In a univariate analysis, age (P=0.03), Karnofsky Performance Status (P=0.0001), stage (P=0.01), HLA A24(9) (P=0.008), HLA B53 (P=0.0006), HLA B63(15) (P=0.01), HLA B64(14) (P=0.01), HLA B65(14) (P=0.01) and HLA CW5 (P=0.01) were significant prognostic factors. In a multivariate analysis, Karnofsky Performance Status (P=0.001), stage (P=0.02), HLA B53 (P=0.03) and HLA B64(14) (P=0.03) were independent prognostic variables. Conclusions: This study demonstrates different HLA types among patients with lung cancer and healthy control subjects. Our results that HLA antigens might affect the prognosis in lung cancer. Further investigations are warranted to delineate any possible role of the HLA system in the pathogenesis and prognosis of lung cancer.
Keywords: HLA Antigens; Lung Neoplasms; Prognosis; Survival; Turkey